Photoluminescence of disordered ABO3 perovskites - Pizani, P. S.; Leite, E. R.; Pontes, F. M.; Paris, E. C.; Rangel, J. H.; Lee, E. J H; Longo, Elson [UNESP]; Delega, P. [UNESP]; Varela, José Arana [UNESP] (AIP Publishing, 2000)
Intense photoluminescence in highly disordered (amorphous) BaTiO3, PbTiO3, and SrTiO3 prepared by the polymeric precursor method was observed at room temperature. The emission band maxima from the three materials are in the visible region and depend on the exciting wavelength. The origin of the photoluminescence was not exactly identified. However, the line shape indicates that confinement effects are not probable. The experimental results indicate that it could be related to the disordered perovskite structure. © 2000 American Institute of Physics.